Novel WC-based metal ceramic composite shielding material and preparation process thereof
Through the composite material process of high-entropy alloy and WC-based ceramics, the problem of insufficient mechanical properties and shielding capabilities of existing WC-based metal cermet composites is solved, and a new type of shielding material with high strength, high hardness and radiation resistance is prepared, suitable for small-scale Radiation protection of nuclear reactors.
Patent Information
- Application Number
- CN202411633699.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
The existing WC-based cermet composites have shortcomings in mechanical properties and shielding capabilities, and it is difficult to meet the needs of small nuclear reactors for high strength, high hardness and radiation resistance.
A new shielding material with excellent mechanical properties, wear resistance, corrosion resistance and radiation resistance was prepared by ball milling mixing, pre-pressing forming and high-temperature and high-pressure sintering.
It realizes a comprehensive shielding material with high strength, high hardness, high wear resistance and corrosion resistance, significantly improves the material's environmental adaptability and electromagnetic shielding performance, and is suitable for radiation protection of small nuclear reactors.
Smart Images

Figure CN119433318A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal-ceramic composite materials for small reactors, and in particular to a novel WC-based metal-ceramic composite shielding material and a preparation process thereof. Background Art
[0002] Small reactors are a key component of nuclear power, and the safe operation of reactors is the guarantee for the effective effect of nuclear power on the system. During nuclear operation, a large amount of α, β, γ, X-rays and certain neutrons will be generated and release energy. The radiated rays and neutrons will not only harm the health of people near the radiation source, but also damage nearby metal materials and electronic equipment. Therefore, it is necessary to take shielding measures for various rays and neutrons generated during nuclear operation. The shielding design problem of small reactors is directly related to whether nuclear energy can be safely used as a power source for the system.
[0003] Among the many types of rays emitted by radioactive sources, the penetration depth of gamma rays and neutrons is much greater than that of other particles. When gamma rays interact with matter, three different effects are mainly produced: photoelectric effect, Compton effect and photoelectric effect. Among them, the photoelectric effect and electron pair effect are that the energy of gamma photons is completely absorbed, while the Compton effect can only make gamma photons lose part of their energy and change the direction of movement of photons until they are all absorbed. Common gamma ray shielding materials include water, concrete, lead, copper, cadmium, iron and plexiglass.
[0004] A scientific and efficient shielding method is to use high atomic number materials, low atomic number materials and neutron absorbing materials for composite shielding. Some nuclear power plants, such as mobile nuclear reactors, require that the shield itself should not be too large or too heavy, and some aspects of the requirements for the shielding material itself are largely contradictory. For example, high thermal stability is often incompatible with the requirement of more hydrogen in the material; the use of high-density materials does not meet the requirements of low cost and high hydrogen content.
[0005] In modern radiation protection scenarios, the increasingly harsh environment and radiation shielding materials require not only excellent thermodynamic properties, but also the shielding of mixed radiation fields of neutrons and gamma rays; the structural components of related nuclear facilities also require materials with excellent high temperature resistance, mechanical properties and radiation resistance. At present, a large number of composite shielding materials have been developed and applied. According to the different matrix, they can be divided into: (1) metal single substance shielding materials; (2) polymer-based comprehensive shielding materials; (3) metal-based comprehensive shielding materials; (4) ceramic-based comprehensive shielding materials; (5) other shielding materials, such as water, shielding concrete, gradient composite shielding materials, etc. However, different shielding materials have their own advantages and disadvantages. Metal-based composite shielding materials have excellent heat resistance, high toughness and radiation resistance, but inorganic fillers such as boron have low solubility in the metal matrix, and excessive filling will seriously reduce the mechanical properties of the matrix; concrete is cheap and has a large adjustable composition, but the shielding rate per unit volume is low, and it can only be used in scenarios where space is not restricted; ceramic materials have good physical and chemical stability, high temperature resistance and radiation resistance, and are environmentally friendly, but due to excessive brittleness, the machinability is reduced. At present, traditional comprehensive shielding materials such as lead plates, boron-containing stainless steel, and lead-boron polyethylene are still widely used, but further research is needed in terms of structural performance, shielding performance, and environmental adaptability. Therefore, there are many difficulties in the research and development of small-scale reactor radiation comprehensive shielding materials, and continued efforts are needed to balance structural performance, shielding performance, and environmental adaptability.
[0006] Existing WC-based metal-ceramic composite materials generally adopt processes such as spark plasma sintering, low-pressure sintering and vacuum sintering, and the metal binder used is generally Co. Liu et al. prepared ultrafine-grained WC-Co cemented carbide with a Co content of 4 to 14wt% by spark plasma sintering. When the Co content is 8wt%, the comprehensive performance of the cemented carbide reaches the best, with a hardness of 19.87GPa, a fracture toughness of 12.27MPa·m1 / 2, and a bending strength of 1834MPa. Azcon et al. prepared nano WC-10Co cemented carbide by hot isostatic pressing technology and found that under the condition of applying 150MPa isostatic pressing, the sintering temperature is 1000℃ to achieve complete densification. Wei et al. prepared WC-10Co cemented carbide by hot isostatic pressing technology and obtained an ultrafine cemented carbide with an average grain size of 430nm, and its hardness and fracture strength were 92.7HRA and 3860MPa, respectively. Yu Xiaohua used hot pressing sintering technology to prepare ultrafine cemented carbide with a WC grain size of 200-300nm. Zhu Qikou et al. used WC-6Co composite powder with an average particle size of 300nm as raw material, and used hot pressing sintering technology to prepare submicron cemented carbide with a density of 99% and a hardness of up to 93HRA. Japan's Sumitomo Coal Mining Company used SPS technology to prepare a gradient WC-based cemented carbide test block with a scale of 100×100×40mm. The surface of the test block is WC-6Co, and the hardness reaches 20GPa. In terms of patents, Co or Ni is currently mainly used as a binder to prepare WC ceramic composite materials. There is no invention patent that uses AlCoCrFeNiCu high entropy alloy as a binder and uses SPS sintering to prepare WC-high entropy alloy composite materials.
[0007] Publication No.: CN117049880A High entropy carbide ceramics for spent fuel shielding materials and preparation methods thereof. The high entropy carbide ceramic material is a (HfNbZrTaW)C5-xZrB2 high entropy ceramic-based material, wherein the metal elements in (HfNbZrTaW)C5 are in an equiatomic ratio, and the mass percentage of ZrB2 is 0-25w%. The designed (HfNbZrTaW)C5-xZrB2 high entropy ceramic-based material is prepared by high-energy ball milling and spark plasma sintering. However, the high entropy carbide ceramic material in this application uses high-cost precious metal raw materials, a complex preparation process, high equipment investment and energy consumption, and the spark plasma sintering method has uneven heating, so the surface and core of the prepared composite material have performance differences, and the production efficiency is low.
[0008] Therefore, a new type of shielding material is urgently needed to solve the problems of insufficient mechanical properties and poor shielding ability of existing WC-based metal-ceramic composite materials. Summary of the invention
[0009] In view of this, the present invention aims to propose a novel WC-based metal-ceramic composite shielding material and a preparation process thereof, so as to solve the problems of insufficient mechanical properties and poor shielding ability of existing WC-based metal-ceramic composite materials.
[0010] In response to the needs of simplifying the shielding design of compact small reactors and reducing the volume of shielding materials, the present invention will provide a new type of comprehensive shielding material with high strength, high hardness, high wear resistance and corrosion resistance for small nuclear reactors and its preparation process. Through the composite optimization design of the components of the shielding material and the use of ultra-high temperature and high pressure sintering process, a high-entropy alloy-WC metal ceramic composite material with excellent mechanical properties, wear resistance, corrosion resistance and radiation resistance is prepared.
[0011] The technical solution of the present invention is achieved in this way:
[0012] The first purpose of the present invention is to disclose a new type of WC-based metal ceramic composite shielding material, which is made of WC-based ceramic powder and high entropy alloy powder through ball milling mixing, pre-pressing molding and high temperature and high pressure sintering. The mass proportion of the high entropy alloy powder in the composite shielding material is 2%-10%.
[0013] Furthermore, the chemical composition content (wt%) of the WC-based ceramic is ≥99.5%, and the chemical composition content (at%) of the high entropy alloy is as follows: Al: 13-18%, Co: 13-18%, Cr: 13-18%, Fe: 13-18%, Ni: 13-18%, Cu: 13-18%.
[0014] Furthermore, the particle size of the WC ceramic powder is 0.4-1.0 μm, and the particle size of the high entropy alloy AlCoCrFeNiCu powder is 3-18 μm.
[0015] Another object of the present invention is to disclose a preparation process of a novel WC-based metal-ceramic composite shielding material, which is used to prepare the novel WC-based metal-ceramic composite shielding material as described in any one of claims 1 to 3, comprising the following specific steps:
[0016] S1: preparing WC ceramic powder and high entropy alloy powder;
[0017] S2: ball milling the WC ceramic powder and the high entropy alloy powder;
[0018] S3: pre-pressing treatment;
[0019] S4: Perform high temperature and high pressure sintering treatment.
[0020] Further, in step S2, the specific steps of ball milling are:
[0021] S21: weighing raw material powder according to proportion, and then adding it into a cemented carbide ball mill;
[0022] S22: Carbide grinding balls are then added to the raw material powders for ball milling, mixing and refining using a planetary ball mill;
[0023] S23: After the ball milling is completed, the mixed slurry is taken out and placed in a distillation bottle, and the ball milling medium therein is removed by means of a rotary evaporator to obtain a dry mixed powder.
[0024] Furthermore, in step S21, the raw material powder is weighed in proportion using an electronic balance with an accuracy of 0.01 mg, and the ball mill and the grinding balls are made of WC hard alloy.
[0025] Further, in step S22, the ball-to-material ratio is set to (3-7):1, the ball milling speed is set to 250-350 rpm, and the forward and reverse rotation mode is adopted, that is, the ball mill first rotates clockwise for 25-35 minutes, then rests for 7-13 minutes, and then rotates counterclockwise for 25-35 minutes, and repeats the process. The ball milling time is 15-50 hours.
[0026] Furthermore, in step S23, during the ball milling process, anhydrous ethanol is selected as the ball milling medium to improve the ball milling efficiency and prevent the powder from being oxidized.
[0027] Furthermore, in step S3, a graphite mold is used for pre-pressing, and the mixed powder is placed in the graphite mold for pre-pressing.
[0028] Furthermore, in step S4, a SPS furnace is used for high temperature and high pressure sintering treatment, with a sintering pressure of 20-60 MPa, a sintering temperature of 1000-1600° C., a heating rate of 40-60° C. / min, and a sintering holding time of 3-13 min.
[0029] Compared with the prior art, the novel WC-based metal-ceramic composite shielding material and its preparation process of the present invention have the following advantages:
[0030] 1. The present invention prepares a new type of comprehensive shielding material with high strength, high hardness, high wear resistance and corrosion resistance through an ultra-high temperature and high pressure sintering process, thereby improving the environmental adaptability of the shielding material, reducing the material volume and optimizing the shielding design.
[0031] 2. The high-strength, high-hardness, high-wear-resistant and corrosion-resistant comprehensive shielding material obtained by the present invention is mainly used for the comprehensive shielding protection of small nuclear reactors, which can effectively shield the radiation potential, and at the same time has good wear resistance, corrosion resistance and strength, and has important engineering application value. Compared with the existing shielding materials, it has the characteristics of good mechanical properties, good shielding performance, and anti-aging. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0033] Figure 1 This is a microscopic morphology of the WC raw material powder of the present invention;
[0034] Figure 2 This is a microscopic morphology diagram of the WC-AlCoCrFeNiCu composite powder of the present invention. DETAILED DESCRIPTION
[0035] In order to make the technical means, objectives and effects of the present invention easy to understand, the embodiments of the present invention are described in detail below with reference to specific drawings.
[0036] It should be noted that all the terms used in the present invention to indicate directionality and position, such as "upper", "lower", "left", "right", "front", "back", "vertical", "horizontal", "inside", "outside", "top", "lower", "lateral", "longitudinal", "center", etc., are only used to explain the relative positional relationship and connection status between the components in a certain state, and are only for the convenience of describing the present invention, rather than requiring the present invention to be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes, and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features.
[0037] In the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0038] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0039] The first purpose of the present invention is to disclose a novel WC-based metal ceramic composite shielding material, wherein the composite shielding material is prepared by ball milling, pre-pressing and high temperature and high pressure sintering of WC-based ceramic powder and high entropy alloy powder.
[0040] High entropy alloys have good electrical conductivity and magnetism, and can effectively shield electromagnetic waves. WC-based ceramics provide structural support and enhance the overall performance of the material. By compounding high entropy alloys with WC-based ceramics, the high entropy alloy can be used to improve the plasticity of the composite material, so that it can maintain good ductility at high temperatures. It can achieve high hardness and high wear resistance while improving electromagnetic shielding performance and the high-temperature stability of the material. High entropy alloys have excellent corrosion resistance.
[0041] This setting combines the advantages of high entropy alloys and WC-based ceramics, achieving high-performance electromagnetic shielding, excellent mechanical properties, good high temperature resistance and excellent corrosion resistance, and can be widely used in aerospace, military and industrial fields.
[0042] Specifically, the mass proportion of the high entropy alloy powder in the composite shielding material is 2%-10%.
[0043] The mass proportion of high entropy alloy powder in this setting is 2%-10%, which can optimize the mechanical properties and corrosion resistance of the material while ensuring the electromagnetic shielding performance, thereby achieving a comprehensive balance of performance.
[0044] Preferably, the mass proportion of the high entropy alloy powder in the composite shielding material is 2%-10%.
[0045] As shown in Table 1-2, specifically, the chemical composition content (wt%) of the WC-based ceramic is ≥99.5%, and the chemical composition content (at%) of the high entropy alloy is as follows: Al: 13-18%, Co: 13-18%, Cr: 13-18%, Fe: 13-18%, Ni: 13-18%, Cu: 13-18%.
[0046] Table 1 Chemical composition and particle size of WC ceramic powder
[0047] Element WC Impurities Content (wt%) ≥99.5 ≤0.5
[0048] Table 2 Chemical composition of AlCoCrFeNiCu high entropy alloy powder
[0049] Element Al Co Cr Fe Ni Cu Content (at%) 13-18 13-18 13-18 13-18 13-18 13-18
[0050] WC-based ceramics provide structural support and enhance the overall performance of the material. The combination of elements such as Al, Co, Cr, Fe, Ni, and Cu gives it a wide-band electromagnetic shielding capability and excellent high-temperature stability. The combination of the two can achieve high hardness and high wear resistance while improving electromagnetic shielding performance, reducing the diffusion rate of atoms and improving the high-temperature stability of the material. The addition of high-entropy alloys improves the plasticity of the composite material, allowing it to maintain good ductility at high temperatures, and can form a stable passivation film on the surface, further improving corrosion resistance.
[0051] This setup combines the advantages of high-entropy alloys and high-purity WC-based ceramics to achieve high-performance electromagnetic shielding, excellent mechanical properties, good high-temperature resistance, and excellent corrosion resistance.
[0052] Specifically, the density of WC-AlCoCrFeNiCu composite material reaches more than 99.5%, the Rockwell hardness is more than 93HRA, the bending strength is more than 1300MPa, the volume wear rate is only 1 / 6 of 316L, no obvious corrosion is observed in neutral salt spray for 720h, and the corrosion rate is less than 10% after 1.5*10 7 After the Gy irradiation test, the hardness and bending strength of the material did not show a significant decrease, the attenuation ratio Ky reached 3.66, and the attenuation coefficient was 0.6486μ / cm -1 .
[0053] The addition of high entropy alloy significantly improves the electromagnetic shielding performance of the material. The attenuation ratio and attenuation coefficient indicate that it has a wide-band electromagnetic shielding capability and can effectively shield electromagnetic waves of different frequencies. The high hardness and high bending strength give the material excellent wear resistance and impact resistance. The low volume wear rate indicates that the material has excellent wear resistance. The excellent corrosion resistance enables the material to maintain stable performance in a corrosive environment. The good radiation stability enables the material to maintain stable performance in a high radiation environment.
[0054] The WC-AlCoCrFeNiCu composite material has very high density, excellent mechanical properties, wear resistance and corrosion resistance, and also performs well in electromagnetic shielding and radiation stability. This material combines the advantages of high entropy alloys and WC-based ceramics to achieve high-performance electromagnetic shielding, excellent mechanical properties, good high temperature resistance and excellent corrosion resistance.
[0055] The second object of the present invention is to disclose a novel preparation process of a WC-based metal-ceramic composite shielding material, comprising the following specific steps:
[0056] S1: Preparation of WC ceramic powder and high entropy alloy powder;
[0057] S2: ball milling the WC ceramic powder and the high entropy alloy powder;
[0058] S3: pre-pressing treatment;
[0059] S4: Perform high temperature and high pressure sintering treatment.
[0060] By controlling the particle size of the powder, the WC ceramic powder and the high entropy alloy powder are fully mixed and uniformly, avoiding local aggregation, improving the performance consistency of the material, forming a uniform composite material, and improving the uniformity of mixing and the density of sintering; through pre-pressing treatment, the mixed powder is pressed into a preform with a certain shape and density, providing a basis for subsequent sintering, and through high temperature and high pressure sintering, the preform undergoes solid phase reaction and liquid phase sintering at high temperature, promoting the interface reaction between WC ceramics and high entropy alloys, forming a good bonding interface, and forming a dense composite material.
[0061] This setting combines high-purity WC-based ceramics and high-entropy alloys through ball milling, pre-pressing, and high-temperature and high-pressure sintering to form a composite material with unique properties. The uniformity and density of the material are ensured, the plasticity of the composite material is improved, and the ductility is maintained at high temperatures. The diffusion rate of atoms is reduced, and the high-temperature stability of the material is improved. The high-entropy alloy can form a stable passivation film on the surface, further improving the corrosion resistance and overall improving the comprehensive performance of the material.
[0062] Specifically, in step S1, the particle size of the WC ceramic powder is 0.4-1.0 μm, and the particle size of the high entropy alloy AlCoCrFeNiCu powder is 3-18 μm.
[0063] As shown in Table 3-4, preferably, the particle size of the WC ceramic powder is 0.6-0.8 μm, and the particle size of the high entropy alloy AlCoCrFeNiCu powder is 5-15 μm.
[0064] Table 3 WC ceramic powder particle size
[0065] powder Particle size distribution / μm WC 0.6-0.8
[0066] Table 4 AlCoCrFeNiCu high entropy alloy powder particle size
[0067] powder Particle size distribution / μm AlCoCrFeNiCu 5-15
[0068] During the sintering process, fine particles are more likely to fill gaps, reduce porosity, and increase the density of the material. They can also increase the contact area between particles to form a tighter structure, thereby improving the hardness and wear resistance of the material. Fine WC particles are easier to mix evenly with other powders to ensure that the performance of the composite material is uniform and consistent; the particle size of the high entropy alloy powder is relatively large, and can form a good mixing uniformity with the fine WC particles; the particle size of the high entropy alloy powder is relatively large, and the fine WC particles can be embedded between the larger high entropy alloy particles to form a uniform composite material; the larger high entropy alloy particles can provide a certain support during the sintering process to prevent the fine WC particles from over-sintering and maintain the microstructure of the material; the larger high entropy alloy particles can provide more conductive paths to improve the electromagnetic shielding performance of the material.
[0069] This setting can significantly increase the density of the material, reduce the porosity, improve the mechanical properties and corrosion resistance of the material, and significantly improve the hardness and wear resistance of the material. It is suitable for occasions that require high hardness and high wear resistance. The fine WC particles can ensure the uniformity of the mixing and improve the performance consistency of the material.
[0070] Specifically, in step S2, the specific steps of ball milling are:
[0071] S21: weighing raw material powder according to proportion, and then adding it into a cemented carbide ball mill;
[0072] S22: Carbide grinding balls are then added to the raw material powders for ball milling, mixing and refining using a planetary ball mill;
[0073] S23: After the ball milling is completed, the mixed slurry is taken out and placed in a distillation bottle, and the anhydrous ethanol therein is removed by means of a rotary evaporator to obtain a dry mixed powder.
[0074] Accurately weighing the raw powder can ensure the consistent performance of each batch of composite materials and avoid performance fluctuations caused by improper proportions; the use of carbide ball mills and planetary ball mills can ensure the uniform mixing of WC ceramic powder and high entropy alloy powder to avoid local aggregation; the ball milling process can further refine the powder particles and improve the density and performance after sintering; the rotary evaporator can effectively remove anhydrous ethanol, ensure the dryness of the mixed powder, avoid excessive humidity affecting subsequent pre-pressing and sintering treatments, and make the mixed powder purer.
[0075] This setting can improve the density and performance after sintering, ensure the performance consistency of the material, avoid the influence of residual solvents on the material properties, and ensure the purity and performance stability of the material.
[0076] Specifically, in step S21, the raw material powder is weighed in proportion using an electronic balance with an accuracy of 0.01 mg, and the ball mill and the grinding balls are both made of WC hard alloy.
[0077] This setting ensures the accurate weighing of the raw powder, avoids weighing errors, and improves the repeatability and reliability of the experiment. At the same time, the high hardness and wear resistance of WC cemented carbide ensure the wear resistance and chemical stability of the ball mill and grinding balls, avoids contamination of the raw powder, and ensures the purity and uniformity of the raw powder.
[0078] Specifically, in step S22, the ball-to-material ratio is set to (3-7):1, the ball milling speed is set to 250-350 rpm, and the forward and reverse rotation mode is adopted, that is, the ball mill first rotates clockwise for 25-35 minutes, then rests for 7-13 minutes, and then rotates counterclockwise for 25-35 minutes, and repeats. The ball milling time is 15-50 hours.
[0079] Preferably, the ball-to-material ratio is set to 5:1, the ball milling speed is set to 300 rpm, and the forward and reverse modes are adopted, that is, the ball milling jar rotates clockwise for 30 minutes, then rests for 10 minutes, and then rotates counterclockwise for 30 minutes, and repeats the process. The ball milling time is 25-40 hours.
[0080] A higher ball-to-material ratio can provide more collision opportunities, effectively crush and refine the powder particles, ensure that the powder particles are fully mixed during the ball milling process, and improve the uniformity of mixing; a higher rotation speed can provide higher energy input, accelerate the crushing and mixing process of the powder particles, ensure that the powder particles are evenly dispersed in the ball mill, and avoid local overheating and local aggregation; the forward and reverse rotation modes can make the powder particles subject to uniform collision and shear force in different directions, improve the uniformity of mixing, and a longer ball milling time can ensure that the powder particles are fully refined and increase the density of the material. A longer ball milling time can ensure that the powder particles are fully mixed during the ball milling process and improve the uniformity of mixing.
[0081] This setting ensures efficient crushing and uniform mixing of powder particles, reduces agglomeration, and improves the material's density, hardness, wear resistance, flexural strength, and electromagnetic shielding performance.
[0082] Specifically, in step S22, the ball mill and the grinding balls are made of YG-6 cemented carbide.
[0083] This setting ensures the high hardness and wear resistance of the ball mill and grinding balls, avoids the generation of wear debris, extends the service life and reduces production costs. At the same time, the high toughness and chemical stability of YG-6 cemented carbide ensure efficient crushing and uniform mixing during the ball milling process, avoids contamination of raw material powder and improves the performance consistency of the material.
[0084] Specifically, in step S23, during the ball milling process, anhydrous ethanol is selected as the ball milling medium to improve the ball milling efficiency and prevent powder oxidation.
[0085] Anhydrous ethanol can form a protective film covering the surface of the powder particles to further prevent oxidation. It can also act as a lubricant to reduce the friction between the powder particles, making the ball milling process smoother and improving the ball milling efficiency. At the same time, it can effectively disperse the powder particles, reduce agglomeration, and ensure that the powder particles are fully mixed and refined during the ball milling process.
[0086] This setting can effectively improve the ball milling efficiency and prevent powder oxidation.
[0087] Specifically, in step S3, a graphite mold is used for pre-pressing, and the mixed powder is placed in the graphite mold for pre-pressing.
[0088] The thermal conductivity of graphite can ensure uniform temperature distribution during the pre-pressing process, reduce temperature gradients, avoid local overheating, and improve the quality of pre-pressing. Good thermal conductivity helps maintain the thermal stability of the mold and ensure the stability and repeatability of the pre-pressing process. The lubricity of graphite can improve the surface finish of the pre-pressed parts and reduce surface defects. The chemical stability of graphite can ensure that the mold will not react chemically with the mixed powder, avoid the introduction of impurities, and ensure the purity of the raw material powder.
[0089] This setting makes full use of the thermal conductivity and lubricity of the graphite mold to improve the quality of pre-pressing, ensure uniform temperature distribution and reduce friction, avoid the introduction of impurities, and ensure the purity of the raw material powder. At the same time, the graphite mold can be designed into complex shapes to meet the molding requirements of different products.
[0090] Specifically, in step S4, a SPS furnace is used for high temperature and high pressure sintering treatment, with a sintering pressure of 20-60 MPa, a sintering temperature of 1000-1600° C., a heating rate of 40-60° C. / min, and a sintering holding time of 3-13 min.
[0091] Preferably, the sintering pressure is 30-45 MPa, the sintering temperature is 1200-1400° C., the heating rate is 50° C. / min, and the sintering holding time is 5-10 min.
[0092] Rapid heating can significantly reduce sintering time, reduce the possibility of oxidation, and ensure the purity of the material. The uniform heating of the SPS furnace can ensure uniform temperature distribution of the sample during the sintering process, avoid local overheating or overcooling, and improve the sintering quality; the close contact of powder particles under high pressure reduces porosity, increases the density of the material, and improves the mechanical properties and electromagnetic shielding properties of the material. At the same time, it can reduce the sintering temperature, avoid grain growth caused by long-term high-temperature treatment, reduce the adverse effects of high temperature on material properties, and extend the service life of the material.
[0093] The rapid heating, uniform heating, high-pressure sintering and short-time sintering characteristics of the SPS furnace can significantly improve the sintering efficiency, reduce the sintering time and improve the density and performance of the material.
[0094] Embodiment 1:
[0095] 0.6μm WC ceramic powder and 10μm AlCoCrFeNiCu high entropy alloy powder (atomic ratio of 1:1:1:1:1:1:1) were ball-milled and mixed (the mass proportion of high entropy alloy powder was 10%). Ball milling process: The ball-to-material ratio was set to 5:1, the ball milling speed was set to 300rpm, and the forward and reverse modes were adopted, that is, the ball mill rotated clockwise for 30 minutes, then rested for 10 minutes, and then rotated counterclockwise for 30 minutes, and repeated. The ball milling time was 40h. After the ball milling was completed, the mixed slurry was taken out and placed in a distillation flask, and the anhydrous ethanol therein was removed by means of a rotary evaporator to obtain a dry mixed powder.
[0096] Then the mold is used for pre-pressing, followed by ultra-high temperature and high pressure (SPS) sintering. The sintering pressure is 30MPa, the sintering temperature is 1200℃, the heating rate is 50℃ / min, and the sintering holding time is 6min. The prepared WC-AlCoCrFeNiCu composite material has a density of 99.75%, a Rockwell hardness of 93.5HRA, and a flexural strength of 1900MPa.
[0097] Example 2
[0098] 0.8μm WC ceramic powder and 5μm AlCoCrFeNiCu (atomic ratio of 1:1:1:1:0.8:0.8) high entropy alloy powder were ball milled and mixed (the mass proportion of high entropy alloy powder was 2%). Ball milling process: the ball-to-material ratio was set to 5:1, the ball milling speed was set to 300rpm, and the forward and reverse modes were adopted, that is, the ball mill rotated clockwise for 30 minutes, then rested for 10 minutes, and then rotated counterclockwise for 30 minutes, and repeated. The ball milling time was 25h. After the ball milling was completed, the mixed slurry was taken out and placed in a distillation flask, and the anhydrous ethanol therein was removed by means of a rotary evaporator to obtain a dry mixed powder.
[0099] Then the mold is used for pre-pressing, followed by ultra-high temperature and high pressure (SPS) sintering. The sintering pressure is 25MPa, the sintering temperature is 1350℃, the heating rate is 50℃ / min, and the sintering holding time is 5min. The prepared WC-AlCoCrFeNiCu composite material has a density of 99.53%, a Rockwell hardness of 94HRA, and a flexural strength of 1400MPa.
[0100] Example 3
[0101] 0.6μm WC ceramic powder and 15μm AlCoCrFeNiCu (atomic ratio of 1:1:1:1:1:1) high entropy alloy powder were ball-milled and mixed (the mass proportion of high entropy alloy powder was 6%). Ball milling process: the ball-to-material ratio was set to 5:1, the ball milling speed was set to 300rpm, and the forward and reverse modes were adopted, that is, the ball mill rotated clockwise for 30 minutes, then rested for 10 minutes, and then rotated counterclockwise for 30 minutes, and repeated. The ball milling time was 35h. After the ball milling was completed, the mixed slurry was taken out and placed in a distillation flask, and the anhydrous ethanol therein was removed by means of a rotary evaporator to obtain a dry mixed powder.
[0102] Then the mold is used for pre-pressing, followed by ultra-high temperature and high pressure (SPS) sintering. The sintering pressure is 40MPa, the sintering temperature is 1400℃, the heating rate is 50℃ / min, and the sintering holding time is 10min. The prepared WC-AlCoCrFeNiCu composite material has a density of 99.68%, a Rockwell hardness of 93.8HRA, and a flexural strength of 1852MPa.
[0103] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A new type of WC-based metal-ceramic composite shielding material, characterized in that: The composite shielding material is prepared from WC-based ceramic powder and high entropy alloy powder by ball milling, pre-pressing and high-temperature and high-pressure sintering. The mass proportion of the high entropy alloy powder in the composite shielding material is 2%-10%.
2. The novel WC-based metal-ceramic composite shielding material according to claim 1 is characterized in that: The chemical composition content (wt%) of the WC-based ceramic is ≥99.5%, and the chemical composition content (at%) of the high entropy alloy is as follows: Al: 13-18%, Co: 13-18%, Cr: 13-18%, Fe: 13-18%, Ni: 13-18%, and Cu: 13-18%.
3. The novel WC-based metal-ceramic composite shielding material according to claim 2 is characterized in that: The particle size of WC ceramic powder is 0.4-1.0 μm, and the particle size of high entropy alloy AlCoCrFeNiCu powder is 3-18 μm.
4. A novel preparation process of WC-based metal-ceramic composite shielding material, characterized in that: The method for preparing the novel WC-based metal-ceramic composite shielding material according to any one of claims 1 to 3 comprises the following specific steps: S1: preparing WC ceramic powder and high entropy alloy powder; S2: ball milling the WC ceramic powder and the high entropy alloy powder; S3: pre-pressing treatment; S4: Perform high temperature and high pressure sintering treatment.
5. The preparation process of the novel WC-based metal-ceramic composite shielding material according to claim 4 is characterized in that: In step S2, the specific steps of ball milling are: S21: weighing raw material powder according to proportion, and then adding it into a cemented carbide ball mill; S22: Carbide grinding balls are then added to the raw material powders for ball milling, mixing and refining using a planetary ball mill; S23: After the ball milling is completed, the mixed slurry is taken out and placed in a distillation bottle, and the ball milling medium therein is removed by means of a rotary evaporator to obtain a dry mixed powder.
6. The preparation process of the novel WC-based metal-ceramic composite shielding material according to claim 5 is characterized in that: In step S21, the raw material powder is weighed in proportion using an electronic balance with an accuracy of 0.01 mg, and the ball mill and grinding balls are made of WC hard alloy.
7. The preparation process of the novel WC-based metal-ceramic composite shielding material according to claim 5 is characterized in that: In step S22, the ball-to-material ratio is set to (3-7):1, the ball mill speed is set to 250-350 rpm, and the forward and reverse rotation mode is adopted, that is, the ball mill first rotates clockwise for 25-35 minutes, then rests for 7-13 minutes, and then rotates counterclockwise for 25-35 minutes, and repeats. The ball milling time is 15-50 hours.
8. The preparation process of the novel WC-based metal-ceramic composite shielding material according to claim 5 is characterized in that: In step S23, during the ball milling process, anhydrous ethanol is selected as the ball milling medium to improve the ball milling efficiency and prevent powder oxidation.
9. The preparation process of the novel WC-based metal-ceramic composite shielding material according to claim 4 is characterized in that: In step S3, a graphite mold is used for pre-pressing, and the mixed powder is placed in the graphite mold for pre-pressing.
10. The preparation process of the novel WC-based metal-ceramic composite shielding material according to claim 4, characterized in that: In step S4, a SPS furnace is used for high temperature and high pressure sintering treatment, with a sintering pressure of 20-60 MPa, a sintering temperature of 1000-1600° C., a heating rate of 40-60° C. / min, and a sintering holding time of 3-13 min.
Citation Information
Patent Citations
High-entropy carbide ceramic for spent fuel shielding material and preparation method of high-entropy carbide ceramic
CN117049880A
Cemented carbide with alternative binder
CN108463301A
High-entropy alloy combined tungsten carbide hard alloy and preparing method thereof
CN110846547A
Continuous casting method of high-entropy alloy
CN112658221A
Application, application performance characterization and preparation method of aluminum-cobalt-chromium-iron-nickel high-entropy alloy
CN113388771A
Cited By
Shielding composite material and preparation method thereof
CN121044903A